1. Rewrite the first equation as x = 2y + 11.
2. Substitute the expression x = 2y + 11 into the second equation.
3. Solve the equation -7(2y + 11) - 2y = -13 for y.
4. Substitute the value of y into the expression x = 2y + 11 to solve for x.
5. The solution to the system of equations is (x, y) = (3, -4).
Put the steps in order that are used to solve the following systems of equations by substitution.%0D%0A%0D%0A−7x−2y=−13%0D%0A−%0D%0A7%0D%0A%0D%0A−%0D%0A2%0D%0A%0D%0A=%0D%0A−%0D%0A13%0D%0Ax−2y=11%0D%0A%0D%0A−%0D%0A2%0D%0A%0D%0A=%0D%0A11%0D%0A(10 points)%0D%0AArrange responses in the correct order to answer the question. Select a response, navigate to the desired position and insert response at that position. Responses can be selected and inserted using the space bar, enter key, left mouse button or touchpad. Responses can be moved using the up and down arrow keys or by dragging with a mouse.%0D%0A%0D%0A−16y−77=−13%0D%0A−%0D%0A16%0D%0A%0D%0A−%0D%0A77%0D%0A=%0D%0A−%0D%0A13%0D%0A%0D%0A−14y−77−2y=−13%0D%0A−%0D%0A14%0D%0A%0D%0A−%0D%0A77%0D%0A−%0D%0A2%0D%0A%0D%0A=%0D%0A−%0D%0A13%0D%0A%0D%0Ax−2(−4)=11%0D%0A%0D%0A−%0D%0A2%0D%0A(%0D%0A−%0D%0A4%0D%0A)%0D%0A=%0D%0A11%0D%0A%0D%0A−16y=64%0D%0A−%0D%0A16%0D%0A%0D%0A=%0D%0A64%0D%0A%0D%0A−7(2y+11)−2y=−13%0D%0A−%0D%0A7%0D%0A(%0D%0A2%0D%0A%0D%0A+%0D%0A11%0D%0A)%0D%0A−%0D%0A2%0D%0A%0D%0A=%0D%0A−%0D%0A13%0D%0A%0D%0Ax−2y=11%0D%0A%0D%0A−%0D%0A2%0D%0A%0D%0A=%0D%0A11%0D%0A --> x=2y+11%0D%0A%0D%0A=%0D%0A2%0D%0A%0D%0A+%0D%0A11%0D%0A%0D%0Ay=−4%0D%0A%0D%0A=%0D%0A−%0D%0A4%0D%0A%0D%0Ax+8=11%0D%0A%0D%0A+%0D%0A8%0D%0A=%0D%0A11%0D%0A%0D%0Ax=3%0D%0A%0D%0A=%0D%0A3%0D%0A%0D%0A(3,−4)%0D%0A(%0D%0A3%0D%0A,%0D%0A−%0D%0A4%0D%0A)
1 answer